Design and Development of a Plastic Bottle-Activated Fan Prototype (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This capstone project, titled "Design and Development of a Plastic Bottle-Activated Fan Prototype," addresses the growing global concern of non-biodegradable plastic waste by integrating discarded materials into a functional electrical system. The study aimed to design a prototype that utilizes plastic bottles as a triggering mechanism to activate a battery-powered fan, evaluating the system's effectiveness and its potential to promote environmental awareness. Using a descriptive-developmental research design, the researchers constructed a model where the insertion of a plastic bottle is acting similarly to a coin-operated mechanism which completes a circuit to power a small DC fan. Testing was conducted at Mindanao State University – Maigo College of Education, Science, and Technology (MSU-MCEST) to measure response time, consistency, and power stability using electrical measurements and observation checklists. Results indicated that the triggering system effectively activated the fan, with the battery providing sufficient and stable power for operation. Participant feedback through a Likert scale evaluation suggested that the prototype serves as an effective educational tool, demonstrating practical waste utilization and the principles of basic automation. The study concludes that simple, low-cost trigger-based systems offer a viable and accessible approach to promoting sustainable waste management and environmental responsibility within a campus setting.